Ecología del Tapir (Tapirus bairdii) en la reserva de la Biosfera La Sepultura, Chiapas, México. - Naranjo Riñera, Eduardo J.; Cruz Aldán, Epigmenio (Instituto de Ecología, A.C., 1998)
The Central American tapir (Tapirus bairdii) has an important role in the dynamica of tropical foresta as a browser, seed dispersar and seed predator; also, it has been a food source for many Mesoamerican cultures for centuries. Nevertheless, this species is endangered because of habitat lose and overhunting throughout its range. In México, the status of tapir populations is virtually unknown, and tíiey are now restricted to a few protected areas in southeastern states. Through sign counts and analyses, and interviews with local inhabitants, we estímated the abundance, habitat preferences, food habits and hunting impact on tapirs in La Sepultura Biosphere Reserve, Chiapas (192,734 ha). This information wili be helpful in order to design a conservation strategy for tapirs in the study area, arxl possibly also in other localities within the Sierra Madre of Chiapas. Tapir evidences (tracks and feces) were more frequently found in subdeciduous and deciduous tropical forest areas (which have more permanent water sources) than in other habitats. Highiy disturbad habitats like grasalands and pine forests were avoided by tapirs, while oak and cloud forests were used as expected. Diet composition was similar to that found in previous studies. although fruit proportion in feces was lees variable throughout the year in La Sepultura. The Information provided by local people suggests that hunting ímpact on tapirs is decreasing in the reserve; however, deforestation rates are still high and habitat fragmentaron is threatening the survival of a healthy tapir population. To avoid the local extinction of tapirs in the study area, we recommend to preserve the remaining forest fragments, to stop the cteation of new settiements within the reserve, and to generate the required Information in order to design a management plan for the protected area.